1994
DOI: 10.2307/1446723
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Strategies and Physiological Adjustments of Reedfrog Tadpoles (Amphibia, Anura, Hyperoliidae) in Relation to Environmental Conditions

Abstract: The relationship between different degrees of intraspecific crowding of reedfrog tadpoles and their physiological responses to a deterioration of the natal pond water quality was examined under laboratory conditions. Tadpoles that were reared at a lower density metamorphosed significantly earlier than those raised at a higher density. As density increases, the average body length at metamorphosis decreases. However, at low tadpole density, a significantly higher diversity of body size classes among freshly met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…We also observed a smaller size in D. galganoi and P. cultripes tadpoles exposed to ammonium nitrate from earlier stages. A decrease in food ingestion as a result of lost activity or an excessive energetic investment in detoxifying mechanisms, such as the urea-ornithine cycle [27], would be some of the possible causes for the smaller size of exposed individuals. Thus, any of these mechanisms should have affected, in a greater way, individuals exposed from earlier developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a smaller size in D. galganoi and P. cultripes tadpoles exposed to ammonium nitrate from earlier stages. A decrease in food ingestion as a result of lost activity or an excessive energetic investment in detoxifying mechanisms, such as the urea-ornithine cycle [27], would be some of the possible causes for the smaller size of exposed individuals. Thus, any of these mechanisms should have affected, in a greater way, individuals exposed from earlier developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many adult frogs are typically limited to microsites with high Forest Ecology and Management 191 (2004) [275][276][277][278][279][280][281][282] humidity, which are found in riparian areas bordering forested streams. Logging can increase the deterioration rate of temporary water sources (streams and pools) by increasing the drying rates and increasing the ammonia concentrations in these water sources, possibly to toxic levels (Schmuck et al, 1994). Many invertebrates also depend on these riparian water sources for egg and larval development.…”
Section: Introductionmentioning
confidence: 99%
“…6 Distribution of body mass of R. temporalis tadpoles in different rearing conditions at metamorphic climax (stages 42-46). Non-identical labels (a,b,c) indicate significant differences from each other (χ 2 test) resources (Rugh 1934;Wilbur 1977a,b;Dash and Hota 1980;Hota and Dash 1981;Jasienski 1988;Schmuck et al 1994;Hokit and Blaustein 1997). These studies showed that generally growth rates, measured in terms of body mass, vary inversely with population density, and slowly growing individuals metamorphose at smaller sizes than their larger conspecifics.…”
Section: Discussionmentioning
confidence: 99%